Comparison of SCATSAT-1 swath data with global in situ buoy winds. Issue 26 (13th December 2022) - Ray, S.; Swain, D.; Patidar, G.; Jayaram, Ch.
Abstract: Indian Space Research Organisation (ISRO) launched SCATSAT-1 scatterometer, on 26 September 2016 as a continuation and enhancement of OSCAT onboard OceanSat-2. The present work carries out a detailed inter-comparison of swath-wise level 2B data from SCATSAT-1 with in situ winds from three moored buoy arrays: Global Tropical Moored Buoy Array (GTMBA), National Data Buoy Center (NDBC) and Ocean Moored Buoy Network for northern Indian Ocean (OMNI). To assess the agreement between the satellite and in situ observations in different regions, the comparison was split between tropical, extra-tropical and coastal regions for each of the global ocean basins. Furthermore, the agreement between the two wind vector datasets was also estimated at each buoy location separately. Poor circular correlations in wind direction (WD) were observed in regions of shallow bathymetry and low mean wind speed, while some WD errors were found to be associated with the failure to resolve directional ambiguity.